Intraplantar aminoglutethimide, a P450scc inhibitor, reduced the induction of mechanical allodynia in a rat model of thrombus-induced ischemic pain - Kwon, Soon-Gu; Choi, Hoon-Seong; Yoon, Seo-Yeon; Roh, Dae-Hyun; Lee, Jang-Hern (BioMed Central, 2024)
Neuroactive steroids (NASs) directly affect neuronal excitability. Despite their role in the nervous system is intimately linked to pain control, knowledge is currently limited. This study investigates the peripheral involvement of NASs in chronic ischemic pain by targeting the cytochrome P450 side-chain cleavage enzyme (P450scc). Using a rat model of hind limb thrombus-induced ischemic pain (TIIP), we observed an increase in P450scc expression in the ischemic hind paw skin. Inhibiting P450scc with intraplantar aminoglutethimide (AMG) administration from post-operative day 0 to 3 significantly reduced the development of mechanical allodynia. However, AMG administration from post-operative day 3 to 6 did not affect established mechanical allodynia. In addition, we explored the role of the peripheral sigma-1 receptor (Sig-1R) by co-administering PRE-084 (PRE), a Sig-1R agonist, with AMG. PRE reversed the analgesic effects of AMG during the induction phase. These findings indicate that inhibiting steroidogenesis with AMG alleviates peripheral ischemic pain during the induction phase via Sig-1Rs.